2020
DOI: 10.1097/md.0000000000022607
|View full text |Cite
|
Sign up to set email alerts
|

IKZF1 polymorphisms are associated with susceptibility, cytokine levels, and clinical features in systemic lupus erythematosus

Abstract: Ikaros family zinc finger 1(IKZF1) encodes a lymphoid-restricted zinc finger transcription factor named Ikaros that regulates lymphocyte differentiation and proliferation as well as self-tolerance. Increasing evidence indicates that IKZF1 could contribute to the pathogenesis of autoimmune diseases. Recent research has provided evidence that IKZF1 might correlate with Systemic lupus erythematosus (SLE), but no clear definition has been made yet. In this study, we focus on the relationship between IKZF1 polymorp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 47 publications
0
9
0
Order By: Relevance
“…These findings demonstrate that two opposing signal transduction pathways, the tumor suppressor PP1 pathway and the oncogenic CK2 pathway, converge on IKAROS and exercise their oncogenic or tumor suppressor effects by controlling its function [ 159 ]. Multiple malignancies, including leukemia, overexpress the multipotent serine/threonine kinase CK2 [ 160 ]. When CK2 is overexpressed in B-ALL, it inhibits IKAROS complex formation and attracts HDAC1 to the BCL2L1 promoter, which represses BCL2L1 and promotes BCL-XL expression [ 161 ].…”
Section: Loss Of Function Of Ikaros In All: What’s Up?mentioning
confidence: 99%
“…These findings demonstrate that two opposing signal transduction pathways, the tumor suppressor PP1 pathway and the oncogenic CK2 pathway, converge on IKAROS and exercise their oncogenic or tumor suppressor effects by controlling its function [ 159 ]. Multiple malignancies, including leukemia, overexpress the multipotent serine/threonine kinase CK2 [ 160 ]. When CK2 is overexpressed in B-ALL, it inhibits IKAROS complex formation and attracts HDAC1 to the BCL2L1 promoter, which represses BCL2L1 and promotes BCL-XL expression [ 161 ].…”
Section: Loss Of Function Of Ikaros In All: What’s Up?mentioning
confidence: 99%
“…The disorder of its expression has the directive relationship with the hematological malignancies and primary immunodeficiency. Lack of Ikaros family may lead to a variety of immune related diseases, including immune thrombocytopenia ( Sriaroon et al, 2019 ), systemic lupus erythematosus ( Chen et al, 2020 ), rheumatoid arthritis ( Yang et al, 2019 ). For example, mutations of IKZF1–3 in leukemias are associated with poor prognosis, mainly caused by the disruption of lymphocyte fates ( Rebollo and Schmitt, 2003 ; Payne and Dovat, 2011 ).…”
Section: Discussionmentioning
confidence: 99%
“… 188 Numerous studies have shown an association between NEAT-1 and SLE. 189 Jiang et al evaluated the expression of NEAT1 in PBMC from patients with SLE and healthy individuals. NEAT1 was shown to be highly upregulated in the PBMC of SLE patients in this research.…”
Section: The Role Of Lncrnas In the Progression Of Slementioning
confidence: 99%